Thinking Outside a Less Intact Box: Thalamic Dopamine D2 Receptor Densities Are Negatively Related to Psychometric Creativity in Healthy Individuals - de Manzano, Örjan; Cervenka, Simon; Karabanov, Anke; Farde, Lars; Ullén, Fredrik (PloS one, 2010)
Several lines of evidence support that dopaminergic neurotransmission plays a role in creative thought and behavior. Here, we investigated the relationship between creative ability and dopamine D2 receptor expression in healthy individuals, with a focus on regions where aberrations in dopaminergic function have previously been associated with psychotic symptoms and a genetic liability to schizophrenia. Scores on divergent thinking tests (Inventiveness battery, Berliner Intelligenz Struktur Test) were correlated with regional D2 receptor densities, as measured by Positron Emission Tomography, and the radioligands [(11)C]raclopride and [(11)C]FLB 457. The results show a negative correlation between divergent thinking scores and D2 density in the thalamus, also when controlling for age and general cognitive ability. Hence, the results demonstrate that the D2 receptor system, and specifically thalamic function, is important for creative performance, and may be one crucial link between creativity and psychopathology. We suggest that decreased D2 receptor densities in the thalamus lower thalamic gating thresholds, thus increasing thalamocortical information flow. In healthy individuals, who do not suffer from the detrimental effects of psychiatric disease, this may increase performance on divergent thinking tests. In combination with the cognitive functions of higher order cortical networks, this could constitute a basis for the generative and selective processes that underlie real life creativity.